2019
DOI: 10.1242/bio.046284
|View full text |Cite
|
Sign up to set email alerts
|

The torso-like gene functions to maintain the structure of the vitelline membrane in Nasonia vitripennis, implying its co-option into Drosophila axis formation

Abstract: Axis specification is a fundamental developmental process. Despite this, the mechanisms by which it is controlled across insect taxa are strikingly different. An excellent example of this is terminal patterning, which in Diptera such as Drosophila melanogaster occurs via the localized activation of the receptor tyrosine kinase Torso. In Hymenoptera, however, the same process appears to be achieved via localized mRNA. How these mechanisms evolved and what they evolved from remains largely unexplored. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The absence of pipe expression in the follicle cells in the honeybee indicates that the loss likely happened early in hymenopteran evolution [ 81 ]. Interestingly, a recent investigation of vitelline membrane proteins in N. vitrpennis [ 95 ] found that their knockdown leads to phenotypes at the cuticular level quite similar to those where the DV axis is disrupted ([ 43 , 96 ], J.A.L., personal observations). This indicates that vitelline membrane components still play a role in establishing DV polarity, but the mechanism and potentially the effect may be different.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of pipe expression in the follicle cells in the honeybee indicates that the loss likely happened early in hymenopteran evolution [ 81 ]. Interestingly, a recent investigation of vitelline membrane proteins in N. vitrpennis [ 95 ] found that their knockdown leads to phenotypes at the cuticular level quite similar to those where the DV axis is disrupted ([ 43 , 96 ], J.A.L., personal observations). This indicates that vitelline membrane components still play a role in establishing DV polarity, but the mechanism and potentially the effect may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Tribolium were dechorionated and fixed as described for Drosophila , but for increased devitellinization efficiency, embryos were passed through a 19G needle in ice-cold 100% methanol. Fixed Nasonia embryos were kindly provided by Shannon Taylor from Peter Dearden’s lab 36 . Parhyale embryos were manually collected from females anaesthetized with 0.01% clove oil in sea water.…”
Section: Methodsmentioning
confidence: 99%
“…Tribolium were dechorionated and fixed as described for Drosophila, but for increased devitellinization efficiency, embryos were passed through a 19G needle in ice-cold 100% methanol. Fixed Nasonia embryos were kindly provided by Shannon Taylor from Peter Dearden's lab 35 . Parhyale embryos were manually collected from females anaesthetized with 0.01% clove oil in sea water.…”
Section: Sample Fixationmentioning
confidence: 99%